In situ detection of alkB2 gene involved in Alcanivorax borkumensis SK2T hydrocarbon biodegradation. Issue 1 (15th September 2016) - Matturro, Bruna; Frascadore, Emanuela; Cappello, Simone; Genovese, Mariella; Rossetti, Simona
Abstract: This study aimed to develop a new assay based on the whole cell hybridization in order to monitor alkane hydroxylase genes ( alkB system) of the marine bacterium Alcanivorax borkumensis SK2 T commonly reported as the predominant microorganism responsible for the biodegradation of n -alkanes which are the major fraction of petroleum hydrocarbons. The assay based on the whole cell hybridization targeting alkB2 gene was successfully developed and calibrated on a pure culture of Alcanivorax borkumensis SK2 T with a detection efficiency up to 80%. The approach was further successfully validated on hydrocarbon-contaminated seawater and provided cells abundance (6.74E + 04  alkB2 -carrying cells mL − 1 ) higher of about one order of magnitude than those obtained by qPCR (4.96E + 03  alkB2  gene copies mL − 1 ). This study highlights the validity of the assay for the detection at single cell level of key-functional genes involved in the biodegradation of n -alkanes. Highlights: Detection at single cell level of genes involved in the biodegradation of n -alkanes Assay calibration on Alcanivorax borkumensis SK2 T showed high detection efficiency. GeneCARD-FISH application on hydrocarbon polluted seawater to detect alkB2 gene